Normal Spermatogenesis in Mice Lacking the Testis-Specific Linker Histone H1t - Lin, Qingcong (American Society for Microbiology, 2000)
H1 histones bind to linker DNA and nucleosome core particles and facilitate the folding of chromatin into a more compact structure. Mammals contain seven nonallelic subtypes of H1, including testis-specific subtype H1t, which varies considerably in primary sequence from the other H1 subtypes. H1t is found only in pachytene spermatocytes and early, haploid spermatids, constituting as much as 55% of the linker histone associated with chromatin in these cell types. To investigate the role of H1t in spermatogenesis, we disrupted the H1t gene by homologous recombination in mouse embryonic stem cells. Mice homozygous for the mutation and completely lacking H1t protein in their germ cells were fertile and showed no detectable defect in spermatogenesis. Chromatin from H1t-deficient germ cells had a normal ratio of H1 to nucleosomes, indicating that other H1 subtypes are deposited in chromatin in place of H1t and presumably compensate for most or all H1t functions. The results indicate that despite the unique primary structure and regulated synthesis of H1t, it is not essential for proper development of mature, functional sperm.